Contesting Space and Representational Politics: State–Community Conflict in the Development of the Suramadu Area - Mutmainnah, Mutmainnah (Society, 2025)
This study explores the contestation of space between the state and local communities in the development of the Suramadu region, particularly the planned construction of a coastal tourism area (Madura Park) in Sekar Bungoh Hamlet, Sukolilo Barat Village, Bangkalan Regency. The research aims to analyze how spatial politics are exercised in the development process, identify the key actors involved, and understand who benefits and who is marginalized in implementing Suramadu's development agenda. Using a qualitative research approach, data were collected through non-participant observation, in-depth interviews with affected residents and government actors, and analysis of planning documents and media coverage. The study is framed by Henri Lefebvre’s theory of the production of space, particularly the concepts of spatial practice, representations of space, and representational space. Findings reveal that the spatial planning of Suramadu's development, articulated through the master plan of the Surabaya–Madura Regional Development Agency (BPWS), prioritizes state and investor interests while marginalizing local communities. The government’s representation of space emphasizes economic growth through tourism, trade, and industrial zones, often at the expense of community rights and historical attachments to the land. The forced displacement and land acquisition processes have generated resistance from residents, who organized through the "Kelompok Masyarakat Tolak Penggusuran" (Community Group Against Eviction) to defend their land, heritage, and livelihoods. Their resistance highlights material grievances and symbolic struggles over recognition, justice, and participation in spatial decision-making. This study concludes that spatial development in Suramadu is marked by structural asymmetries of power, in which space becomes a site of political contestation rather than shared progress. It also underscores the importance of participatory and culturally informed spatial planning to mitigate conflict and ensure equitable development outcomes.